Natural Resource Policy and Indigenous Peoples' Rights in the Era of Decarbonisation - Reza Fauzi Nazar; Farah Nasser; Alif Ramadhan; Efi Lismiyah; Dewi Putriani Yogosara Lodewijk (Jurnal Pelita Raya, 2026)
Amidst the global euphoria surrounding the transition to a low-carbon economy, decarbonisation is in fact ushering in a new chapter in the politics of natural resources. This study aims to analyse the relationship between the global decarbonisation agenda and the politics of natural resource management in Indonesia, with a particular focus on its implications for the rights of indigenous peoples. This study employs a qualitative, critical case study design, given that the phenomenon is complex, contextual, and involves power relations that a purely quantitative approach cannot adequately explain. The findings confirm that decarbonisation not only brings about an energy transition but also creates new political arenas in the struggle for authority over territories and natural resources, where the state, the global market, and the carbon regime form a configuration of power that risks reproducing the logic of extractivism in a greener guise. The energy transition, which is normatively promoted as a solution to the climate crisis, risks creating an ecological-political paradox as strategic mineral projects, green industrial zones, and market-based carbon economies expand institutional control over forests and indigenous territories that have long served as the foundation for ecosystem sustainability. The conflict between climate mitigation and the sovereignty of indigenous communities is not an anomaly but a structural consequence of integrating nature into the logic of the carbon market and the industrialisation of clean energy.